The reliability of ten-meter sprint time using different starting techniques - Duthie, G. M.; Pyne, D. B.; Ross, A. A.; Livingstone, S. G.; Hooper, S. L. (The Journal of Strength and Conditioning Research, 2006)
Acceleration is an important factor for success in team-sport athletes. The purpose of this investigation was to compare the reliability of 10-m sprint times when using different starting techniques. Junior male rugby players (n = 15) were tested for speed over 10 m on 2 different testing sessions. Three trials of 3 different starting techniques (standing, foot, and thumb starts) were assessed. Despite large differences in the time taken to perform 10-m sprints from different starts, there was minimal difference in the typical error (0.02 seconds, or <1%) between the 3 different starts. There was a small, 0.02 ± 0.02 second, decrease (p = 0.05) in sprint time between sessions for the foot start. For all starting techniques, the magnitude of error (typical error) was greater than the smallest worthwhile change (<0.01 second), indicating that acceleration over 10 m measured by photocells only has a marginal chance of reliably detecting a change of sufficient magnitude to be worthwhile in practical terms. However, by accounting for the smallest worthwhile change and typical error, it is possible to establish the probability an individual has had a worthwhile change in sprint performance. Coaching and sports-science practitioners can use a variety of sprint-start techniques shown to have small typical errors (<1%); however, the results from the different starting technique are not interchangeable.